2018
DOI: 10.1038/s41598-018-25659-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electrical properties of the p-type transparent conducting oxide Cu1−xCr1+xO2 by controlled annealing

Abstract: Off-stoichiometric copper chromium oxide delafossite received lately a great interest due to its high p-type electrical conductivity and adequate optical transmittance in the visible range. However, for a suitable integration in active devices such as p-n junctions, transistors or optoelectronic devices, the electronic properties must be efficiently tailored. Here, post-deposition thermal treatment is proven as an adequate approach for finely controlling the electrical properties of this former degenerate semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…Films present high electrical conductivities, that leads to an ohmic behaviour of the junction, showing a non-rectifying response as later described. The annealing effects on the delafossite have been reported in our previous work [17]. A decrease of the carrier concentration for temperatures above 650 °C was observed.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Films present high electrical conductivities, that leads to an ohmic behaviour of the junction, showing a non-rectifying response as later described. The annealing effects on the delafossite have been reported in our previous work [17]. A decrease of the carrier concentration for temperatures above 650 °C was observed.…”
Section: Resultssupporting
confidence: 71%
“…This model explains thus the higher holes mobility (above 1 cm 2 V −1 s −1 ) achieved in this type of materials when comparing with other TCOs [18]. Among copper delafossites, CuCrO 2 presents a high density of states of 3d cations (Cr 3+ ) near the valence band maximum allowing thus the covalent mixing between the chromium and oxygen atoms and a good dopability [17]. The interest in these particular materials has grown since Nagarajan et al [19] reported the highest conductivity (220 S cm −1 ) of delafossite compounds for Mg doped CuCrO 2 whilst they measured an optical transparency of 30% in the case of 270 nm thin films.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Alternative methods, with larger scattering cross-section and sensitivity to local bond structures, rather than long-range order, are hence sought for. Particularly for recently developed amorphous or non-crystalline p-type TCOs gaining additional information on the local bond structure will be helpful to gain insights on the doping mechanisms [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%